2018
DOI: 10.3989/gya.0217181
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted extraction of non-polar compounds from pistachio hull and characterization of extracts

Abstract: Soxhlet and microwave assisted extraction (MAE) methods were used to obtain non-polar compounds from pistachio hull. MAE parameters (liquid to solid ratio, microwave power, and extraction time) were studied to obtain maximum extraction yield. The optimal conditions were found to be liquid to solid ratio of 15:1 (v/w), microwave power of 250 W and extraction time of 12.5 min. The extraction yields were 9.81 and 9.50% for MAE and Soxhlet methods, respectively. The total phenolic content, antioxidant activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For different power levels, there was a general increase in oil recovery with an increase in time from 5 to 15 min and substrate ratio from 1:3 to 1:8. Additionally, the substrate ratio from pistachio hull using MAE was optimum at a microwave power of 250 W for 12.5 min and a solid to solvent ratio of 1:15 (Ozbek et al, 2018). These studies show that the yield and optimum conditions for MAE are all within a given range, with variations being attributed to the target compound.…”
Section: Microwave-assisted Extraction (Mae) Of Mango Kernel Oilmentioning
confidence: 75%
“…For different power levels, there was a general increase in oil recovery with an increase in time from 5 to 15 min and substrate ratio from 1:3 to 1:8. Additionally, the substrate ratio from pistachio hull using MAE was optimum at a microwave power of 250 W for 12.5 min and a solid to solvent ratio of 1:15 (Ozbek et al, 2018). These studies show that the yield and optimum conditions for MAE are all within a given range, with variations being attributed to the target compound.…”
Section: Microwave-assisted Extraction (Mae) Of Mango Kernel Oilmentioning
confidence: 75%
“…Despite its scarce applicability to almond and by-products thereof, MAE has been successfully applied to the extraction of phenolic compounds from other tree nuts and corresponding by-products such as Pistacia vera and Anacardium occidentale. In general, the power used in compounds extraction from nuts by-products could reach values ranging from 100 to 1000 W, generally associated with short extraction times (between 1 to 12.5 min), despite it can reach up to 1 h [45,62,63]. Additionally, MAE has been used in other species from the same genus, such as Prunus armeniaca L., for protein extraction purposes [62].…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
“…6 Recently, several studies were performed to extract and characterise the essential oil extracted from nutshells, leaves, peels, seeds of different fruits, and nuts [7][8][9][10][11][12]. These methods include solvent extraction, ultrasound-assisted extraction, supercritical fluid extraction, and microwave-assisted extraction [13][14][15]. Goli et al reported that the extracted oil with a concentration of 0.06% has a similar effect to synthetic antioxidants such as butylated hydroxyanisole (BHA) and butyl-hydroxytoluene (BHT) [13].…”
Section: Introductionmentioning
confidence: 99%